FIXED OILS OF MEXICO II CAOBA SWIETENIA MACROPHYLLA KINA - MUNGUIA B, RICARDO; MILLARES, R; LLOYD, WR; GURLEY, NF (ARMOUR RESEARCH FOUNDATION, INTERNATIONAL DIVISION, CD. MEXICO, D F, MEX, 1949)
The physical and chemical characteristics of the oil of the caoba seed (S. macrophylla Kina) have been reported. The composition of the oil has been calculated. Â© 1949 American Oil Chemists' Society.
J AM OIL CHEM SOC
Keywords: FIXED, OILS, MEXICO, CAOBA; QUIMICA; BIOQUIMICA; ACEITES FIJOS